Bentham's Utilitarianism Ethical Theory and Its Application in the Triage System: A Scholarly Philosophical Paper - Basheer Al-Zu'bi; Amal Ababneh; Fourat Altarawneh; Nour Alrida (Jordan University of Science and Technology, 2024)
Background: Jeremy Bentham introduced Utilitarianism which is one of the normative ethical theories that imposes procedures that maximize happiness and well-being for all intended individuals. Utilitarianism has been applied to the crisis of global poverty, the ethics of raising animals for food, and social welfare economics. Materials and Methods (2023): In the current paper, we study the concept of Utilitarianism in the Triage system in disasters as an example of a nursing healthcare system. Results: Utilitarianism is a practical framework for the Triage system. Because it represents an important style of thought in modern life. Conclusions: Utilitarianism could be applied in some situations such as pandemics and crises. However, it has some limitations related to the ignorance of the principles of human rights and social justice.